Effects of Type 2 Diabetic Serum on Proliferation and Osteogenic Differentiation of Mesenchymal Stem Cells - Xiangqun Deng; Min Xu; Moyu Shen; Jinluo Cheng (Journal of Diabetes Research)
Diabetic patients have an increased risk of osteoporosis-associated fractures. However, the results of most studies of the effects of diabetes on bone mass in patients with type 2 diabetes (T2DM) have been contradictory. To clarify these conflicting findings, we investigated the effects of diabetic serum on the proliferation and osteogenic differentiation of mesenchymal stem cells (MSCs). We used human sera from subjects with different levels of glycemic control to culture the MSCs and induce osteogenic differentiation. The rate of MSC proliferation differed when MSCs were cultured with sera from diabetic subjects with different levels of hyperglycemia. Hyperglycemic sera promoted MSC proliferation to some extent, but all the diabetic sera inhibited the differentiation of MSCs to osteoblasts. The effects of type 2 diabetic sera on the proliferation and osteogenic differentiation of MSCs are closely related to glycemic control. Our data demonstrate the importance of stratifying the study population according to glycemic control in clinical research into diabetic osteoporosis.